Penerapan Model Problem-Based Learning terhadap Kemampuan Berpikir Kritis Matematis Siswa - Sudarmono Sudarmono (REGRESI: Journal of Mathematics Education and Application, 2025)
This study aims to analyze the effect of implementing the Problem-Based Learning (PBL) model on students’ mathematical critical thinking skills. Critical thinking is one of the essential competencies in mathematics education, as it plays a significant role in developing analytical skills, evaluation, logical reasoning, and evidence-based decision-making. However, mathematics instruction in schools still tends to focus on procedural learning and memorization, providing limited opportunities for students to develop higher-order thinking skills. This research employed a quantitative approach with a quasi-experimental design using a pretest–posttest control group design. The research sample consisted of two classes: an experimental class that received instruction through the PBL model and a control class that was taught using conventional methods. The research instrument was a mathematical critical thinking test that had been validated and tested for reliability. The data were analyzed using inferential statistical tests, specifically the independent samples t-test, to determine differences in improvement between the two groups. The results indicate that the implementation of the PBL model has a significant effect on improving students’ mathematical critical thinking skills. Students who learned through PBL demonstrated greater improvement compared to those who received conventional instruction. These findings suggest that the PBL model is effective in encouraging students to actively identify problems, analyze information, and systematically construct solutions in mathematics learning.